With the Jewish orientalist Joseph Eliash In his research on Imam Hassan Al-Askari (View and critique) (Journal of Misan Researches, 2024)
Orientalist studies of Islam have been around for a long time, dating back to centuries of Islamic history, but Western academic and methodological research on Shiites is only a century old .It has grown significantly in the last decades of the last century with various motives, most of which dealt with Shiite beliefs, the biography of the Imams and their history Among the academic works that gained the attention of the West and its Orientalist schools is the Encyclopedia of the Islamic Encyclopedia, in which research on the infallible Imams (peace be upon them) was devoted, including the study “Imam Hassan Al-Askari (peace be upon him)” by the Jewish Orientalist “Joseph Al-Yash. Although it contains valuable information about the Imam (peace be upon him), it is a very brief study. The researcher in it overlooked important stations in the life of Imam Al-Askari, peace be upon him, such as the persecution of the political authority ruling him, his role in raising awareness, educating and preparing his followers, and confronting deviant ideas and trends. If the researcher had relied on advanced and modern Shiite sources, he would not have encountered these problems that omitted many of the historical facts of Imam Al-Askari.